The effect of photovoltaic panels on the microclimate and on the tomato production under photovoltaic canarian greenhouses. (October 2018) - Ezzaeri, K.; Fatnassi, H.; Bouharroud, R.; Gourdo, L.; Bazgaou, A.; Wifaya, A.; Demrati, H.; Bekkaoui, A.; Aharoune, A.; Poncet, C.; Bouirden, L.
Highlights: Study of the adaptation of the PV panels to the canarian greenhouses. Study of the PV panel effects on the microclimate under the canarian greenhouse. Study of the PV panel on the tomato production under the canarian greenhouse. Investigation on the of the PV panel effects on the development of T. absoluta . No significant effect on the climatic parameters with 10% of PV panel occupancy rate. No significant effect on the agronomic parameters with 10% of PV panel occupancy rate. Abstract: Photovoltaic greenhouses are mixed systems, combining electricity and agricultural production in the same area. Moreover, this type of greenhouse conserves all the properties of a conventional greenhouse, as well as offering the possibility of producing and selling electricity. The aim of the present study is to assess both the impact of the shade caused by the photovoltaic panels on the microclimate and the quality of fruits in the greenhouse. Measurements were carried out in an experimental Canary type greenhouse covered with flexible photovoltaic panels on 10% of its total roof area. Results illustrate that this occupancy rate of the photovoltaic panels arranged in checkerboard pattern does not have a significant effect on the agronomic parameters e.g. height, stem diameter and tomato yield, and climatic parameters under the greenhouse cover. Additionally, the presence of photovoltaic panels has a negative effect on the development of the population of Tuta absoluta .